The Influence of Leadership on Employee Work Motivation at the One-Stop Integrated Administration System (Samsat) Office in Gowa Regency - Rahmika Angraini Jum; Dg. Maklassa; Sri Andayaningsih (Yayasan Amerta Insan Unggul, 2026)
This study examines the influence of leadership on employee work motivation in a public sector organization, specifically at the One-Stop Integrated Administration System (SAMSAT) Office in Gowa Regency. Although leadership has been widely recognized as a key determinant of employee motivation, empirical findings remain inconsistent, and limited studies have specifically explored this relationship within regional SAMSAT offices. This study adopts a quantitative explanatory approach using a saturated sampling technique involving 43 employees. Primary data were collected through structured questionnaires and observations, while secondary data were obtained from institutional documentation and literature. The data were analyzed using simple linear regression with SPSS version 27. The findings indicate that leadership has a positive and significant effect on employee work motivation, as demonstrated by a t-value of 6.153 exceeding the critical value of 1.681, with a significance level of 0.000. The regression coefficient (0.582) shows that improvements in leadership quality are associated with increased employee motivation. Furthermore, the coefficient of determination (R²) reveals that leadership explains 48% of the variation in employee work motivation. These results highlight the importance of leadership effectiveness in fostering employee enthusiasm, responsibility, and organizational commitment. This study contributes to the human resource management literature by providing focused empirical evidence on the direct role of leadership in shaping work motivation within a public service context. Practically, the findings offer strategic insights for organizational leaders and policymakers to enhance employee motivation and improve public service performance.